Development of Digital Comic Media Based on Problem-Based Learning (PBL) Model in Pancasila Education for Fourth Grade Students at Elementary Schools - Melfira Sarki; Reinita Reinita (Green Publisher Indonesia, 2024)
The rapid advancement of technology, particularly within the framework of the industrial revolution 4.0, necessitates the integration of technology into the educational sector to enhance learning processes. This study focuses on developing a Problem-Based Learning (PBL) based digital comic medium for teaching Pancasila Education elements in fourth-grade elementary school students. Utilizing the ADDIE development model, this research encompasses analysis, design, development, implementation, and evaluation phases. Validation tests with material, linguistic, and media experts indicated high validity, while practicality tests with teachers and students demonstrated strong practicality. Effectiveness tests revealed significant improvements in student engagement and learning outcomes. The results suggest that the digital comic medium is a viable, practical, and effective educational tool that enhances student comprehension and character development.